Development of an upwind sailing ergometer - Callewaert, M.; Geerts, S.; Lataire, E.; Boone, J.; Vantorre, M.; Bourgois, J. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To develop a sailing ergometer that accurately simulates upwind sailing exercise. Methods: A sailing ergometer that measures roll moment accompanied by a biofeedback system that allows imposing a certain quasi-isometric upwind sailing protocol (ie, 18 bouts of 90-s hiking at constantly varying hiking intensity interspersed with 10 s to tack) was developed. Ten male high-level Laser sailors performed an incremental cycling test (ICT; ie, step protocol at 80 W + 40 W/3 min) and an upwind sailing test (UST). During both, heart rate (HR), oxygen uptake (VO2), ventilation (VE), respiratory-exchange ratio, and rating of perceived exertion were measured. During UST, also the difference between the required and produced hiking moment (HM) was calculated as error score (ES). HR, VO2, and VE were calculated relative to their peak values determined during ICT. After UST, the subjects were questioned about their opinion on the resemblance between this UST and real-time upwind sailing. Results: An average HM of 89.0% ± 2.2% HMmax and an average ES of 4.1% ± 1.8% HMmax were found. Mean HR, VO2, and VE were, respectively, 80% ± 4% HRpeak, 39.5% ± 4.5% VO2peak, and 30.3% ± 3.7% VEpeak. Both HM and cardiorespiratory values appear to be largely comparable to literature reports during on-water upwind sailing. Moreover, the subjects gave the upwind sailing ergometer a positive resemblance score. Conclusions: Results suggest that this ergometer accurately simulates on-water upwind sailing exercise. As such, this ergometer could be a great help in performance diagnostics and training follow-up.